Black:white inequities in infant mortality across the 69 most populous US cities, 2018–2021 - Saiyed, Nazia S.; Bishop-Royse, Jessica C.; Smart, Britney P.; Leung, Anne; Benjamins, Maureen R. (Frontiers in Public Health, 2025)
The United States has poor birth outcomes, including high rates of infant mortality and substantial racial inequities, compared to other developed nations. However, both overall mortality rates and racial inequities in rates vary across locations, emphasizing the structural forces that shape population health. We used mortality and natality data from the National Vital Statistics System to assess racial inequities in infant mortality rates within the most populous US cities for 2018–2021. Specifically, we: (1) calculate overall and race-specific infant mortality rates for 69 cities and racial inequities in infant mortality for 48 cities; and, (2) analyze associations between these inequities and city-level measures of structural racism. City-level infant mortality rates ranged from 1.96 deaths per 1,000 births in Irvine, CA to 13.92 in Detroit, MI. The non-Hispanic Black infant mortality rate was 2.5 times higher than the non-Hispanic white rate in the US and the Black:white rate ratio was statistically significant in all study cities, ranging from 1.8 (Omaha, NE) to 5.0 (Cincinnati, OH). The Black:white rate ratio was greater than 4.0 in 10 cities. Overall and race-specific infant mortality rates were associated with measures of education, economic status, incarceration, segregation, and diversity. Racial inequities in infant mortality were associated with measures of economic status. Understanding infant mortality inequities at the city level is critical to support the efforts of urban health advocates. Moreover, examining the persistent associations of structural racism with infant mortality will help guide necessary programmatic or policy decisions to reduce infant mortality in US cities.